Wordwall Application in Improving Numeracy Ability SDN RENDA - Juniarti, Selfi; Syarifudin, Syarifudin; Nurrahmah, Nurrahmah (Jurnal Ilmiah Mandala Education (JIME), 2024)
Education plays a crucial role in developing individual potential and enhancing quality of life, with numeracy skills being a key aspect of this process. This study aims to explore the effectiveness of using the Wordwall application in mathematics learning to improve numeracy skills among students at SDN Renda. A qualitative approach with a descriptive case study design was employed. Data were collected through observations, interviews with teachers and students, and documentation. The results indicate that the use of Wordwall significantly increased student engagement and motivation, with an average posttest score improvement of 20.4 points compared to the pretest. The application offers various quiz and game templates that make learning more interactive and engaging. However, challenges related to technology access limited the full implementation of the application. The discussion highlights that Wordwall is effective in enhancing mathematics understanding and numeracy skills, as well as increasing student interest in learning. In conclusion, Wordwall is a highly beneficial tool in mathematics education, and schools should provide technological support and training for teachers to maximize its benefits. The study recommends broader implementation of the Wordwall application to improve the quality of mathematics education in elementary schools.